2001
DOI: 10.1007/s004280000333
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic changes of thymoma preoperatively treated with corticosteroids

Abstract: Preoperative treatment of thymoma in advanced stages with corticosteroids may reduce the size of the tumor, but no precise histologic evaluation has been performed. We examined the histopathologic features of pretreatment biopsy and posttreatment surgical specimens of eleven cases of thymoma with such treatment to see the changes of the histologic subtypes based on Muller-Hermelink classification. All specimens were also assessed immunohistochemically for MIB-1 labeling and apoptotic cells to verify the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Epithelial cell proliferation in thymoma may be regulated by other cellular components, such as thymocytes, macrophages, and dendritic cells (Masuda et al 1990). Thus, some degenerative changes in epithelial cells following glucocorticoid therapy may also be secondary to the depletion of thymocytes and the consequent defects in thymocyte-epithelial interactions (Tateyama et al 2001). To confirm the susceptibility of neoplastic TECs, we extended previous studies to tumor cells isolated from thymoma tissues in primary cultures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Epithelial cell proliferation in thymoma may be regulated by other cellular components, such as thymocytes, macrophages, and dendritic cells (Masuda et al 1990). Thus, some degenerative changes in epithelial cells following glucocorticoid therapy may also be secondary to the depletion of thymocytes and the consequent defects in thymocyte-epithelial interactions (Tateyama et al 2001). To confirm the susceptibility of neoplastic TECs, we extended previous studies to tumor cells isolated from thymoma tissues in primary cultures.…”
Section: Discussionmentioning
confidence: 98%
“…Tateyama et al (Tateyama et al 2001) obtained similar results from TUNEL staining of sections, and suggested that glucocorticoids may have a suppressive A (a, b), AB (c, d), B1 (e, f), B2 (g, h), and B3 (i, j) thymoma tissues were stained with anti-GR (a, c, e, g, i), or anti-cytokeratin (b, d, f, h, j). GR expression was shown in both thymocytes and epithelial cells (路400) effect on the epithelial as well as the lymphocyte component of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…22 Systemic LPS challenge results in a rise in plasma corticosterone levels and a pro-inflammatory cytokine cascade, which contribute to thymic involution via the preferential loss of thymocytes and characteristic remodelling of thymic stromal architecture. 23,24 The interplay between the supporting stromal environment and developing thymocytes has been well described and is considered to be crucial for robust thymopoiesis to occur. 25 Several studies using bone marrow chimeras have also speculated that leptin receptor expression on radioresistant thymus stroma may be important for thymic homeostasis during hypercorticosteronaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Tateyama et al reported fungal infection as a side effect of steroids. 7 On the other hand, Funakoshi and colleagues described a potential mechanism of regression of thymomas by corticosteroids, indicating that neoplastic thymic epithelial cells express glucocorticoid receptors and that glucocorticoids directly induce G 1 cell cycle arrest and apoptosis. 8 Unfortunately, only 2 months after the regression our patient died of rapid progression of interstitial pneumonitis.…”
Section: Commentmentioning
confidence: 97%
“…6 Tateyama et al reported that corticosteroid therapy may cause degenerative changes in some thymomas. 7 However, corticosteroid therapy, especially in high-dose or long-term therapy, should be considered cautiously because of various side effects. Tateyama et al reported fungal infection as a side effect of steroids.…”
Section: Commentmentioning
confidence: 99%